Hydrodechlorination of 1,2-dichloroethane by rhodium catalysts under water gas shift reaction conditions - Trabuco, E.; Ford, P. C. (Elsevier B.V., 1999)
Homogeneous catalysts prepared from rhodium trichloride in aqueous aromatic amines have been shown to reduce C-CI bonds under mild water gas shift conditions (T=100 degrees C, P-CO = 1.0 atm). In a 4-picoline/water solvent mixture, 1,2-dichloroethane is reduced to ethylene and ethane in yields compatible with the consumption of the reducing agent CO and with the formation of CO2. Variation of the catalyst solutions by using different substituted pyridines shows a pattern of catalytic activity parallel to that reported previously for H-2 production from the shift reaction, There is a moderate dependence of activity on the basicity of the aromatic amine, but a methyl group at the alpha-position exercises a strong negative steric effect. Long term studies show decrease of the activity with the time perhaps due to the build up of chloride in the medium. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: hydrodechlorination; 1,2-dichloroethane; rhodium catalysts